Preliminary Study on Petrography and Geochemistry of Granitic Rocks in the Khao Phra - Khao Sung area, Amphoe Nong Bua, Changwat Nakhon Sawan, Central Thailand - Fanka, Alongkot; Nakapadungrat, Somchai (Bulletin of Earth Sciences of Thailand, 2021)
Granitic rocks exposed Khao Phra - Khao Sung area, Amphoe Nong Bua, Changwat Nakhonsawan are one of an important part of the magmatic rocks in central Thailand to understand the magmatism and tectonics. The granitic rocks can be classified into monzodiorite and alkali granite/syenite. The monzodiorite is dominated by plagioclase, quartz, K-feldspar, Biotite, and some accessory minerals and clearly presents ophitic texture. The alkali granite/syenite is composed of mainly K-feldspar, quartz, plagioclase, and biotite. Moreover, the graphic intergrowth texture of quartz and K-feldspar together with perthitic texture of K-feldspar and albite are clearly observed in the alkaline granite/syenite. Geochemically, these granitic rocks have different compositions as herein nomenclature. However, both monzodiorite and alkali granite/syenite can be classified into I-type granite and were formed by hydrous calc-alkaline magma related to arc subduction of Palaeo-Tethys beneath Indochina Terrane. In addition, these granitic rocks are comparable with the Eastern Belt Granite of Thailand together with corresponding to the Loei Fold Belt.